Protocol: evaluation of an optimised couples-focused intervention to increase testing for HIV in rural KwaZulu-Natal, South Africa, the Igugu Lethu ('Our treasure') cohort study - Nuala McGrath; Nathi Ngcobo; Zhixin Feng; Phillip Joseph; Pumla Dladla; Thulani Ngubane; Victoria Hosegood; Katherine Morton; Heidi Van Rooyen; Alastair Van Heerden (BMC, 2022)
Abstract Background Between 2012 and 2015, the Uthando Lwethu (UL) study demonstrated that a theory-based behavioural couples-focused intervention significantly increased participation in couples HIV testing and counselling (CHTC) among South African couples who had never previously tested for HIV together or mutually disclosed their HIV status, 42% compared to 12% of the control group at 9 months follow-up. Although effective, we were nonetheless concerned that in this high prevalence setting the majority (58%) of intervention couples chose not to test together. In response we optimised the UL intervention and in a new study, 'Igugu Lethu', we are evaluating the success of the optimised intervention in promoting CHTC. Methods One hundred eighty heterosexual couples, who have been in a relationship together for at least 6 months, are being recruited and offered the optimised couples-focused intervention. In the Igugu Lethu study, we have expanded the health screening visit offered to couples to include other health conditions in addition to CHTC. Enrolled couples who choose to schedule CHTC will also have the opportunity to undertake a random blood glucose test, blood pressure and BMI measurements, and self-sample for STI testing as part of their health screening. Individual surveys are administered at baseline, 4 weeks and 4 months follow-up. The proportion of couples who decide to test together for HIV will be compared to the results of the intervention arm in the UL study (historical controls). To facilitate this comparison, we will use the same recruitment and follow-up strategies in the same community as the previous UL study. Discussion By strengthening communication and functioning within the relationship, the Igugu Lethu study, like the previous UL study, aims to transform the motivation of individual partners from a focus on their own health to shared health as a couple. The Igugu Lethu study findings will answer whether the optimised couples-focused behavioural intervention and offering CHTC as part of a broader health screening for couples can increase uptake of CHTC by 40%, an outcome that would be highly desirable in populations with high HIV prevalence. Trial registration Retrospectively registered. ISRCTN Registry ISRCTN 46162564 Registered on 26th May 2022.